THE FORMATION OF THE LEAF SURFACE OF SOY SEEDING DEPENDING ON THE VARIETY, METHOD OF SOWING AND SEEDING RATE IN LOW MOISTURE OF FOREST-STEPPE - Лотиш, І. І. (Scientific Progress & Innovations, 2017)
Getting the maximum possible productivity of any sort of soybeans depends on the component technologies that provide optimal formation of leaf surface and duration of photosynthetic activity. The study of photosynthetic potential of crop soybean sorts showed that the highest rate was in the areas with a seeding rate of 800 thousand/ha: row planting sowing – 2,19–2,34 million m2 days/ha for sowing in wide row – 2,16–2,27 million m2 day/ha. The intensity of photosynthesis depending on the options ranged experiment: the row planting method in the range of 11,55 to 12,40 mg CO2 dm2/day wide row planting way – from 11,33 to 12,06 mg CO2 dm2/h. Depending on the seeding rate and method of sowing was layered index according to the sorts: Romantyka – from 3,89 to 4,13 m2 leaf/m2, Ustya – from 3,88 to 3,99, Vorskla – from 3,80 to 3,92 leaf m2/m2.